STUDI KEPATUHAN PASIEN DIABETES MELLITUS RAWAT JALAN di RSUD KABUPATEN SIDOARJO - Efer Memento Yotlely Romera; Angelica Kresnamurti; Dyah Ayu Febiyanti (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2021)
Diabetes mellitus is a metabolic disease that has symptoms due to elevated blood glucose levels above normal values and requires regular treatment. Patient adherence is very important to reduce the risk of complications in diabetes mellitus patient. This research aims to determine correlation the patient adherence in taking antidiabetic drugs with two different methods, Pill count and MMAS-8 method. This research used cross-sectional with non-probability sampling methods. There were 21 outpatients in Sidoarjo Hospital included in this research. Based on the result by pill count, obtained 14 respondents adherent (66.67%) and non-adherent respondents was 7 (33.33%), while the result of MMAS-8 method was 8 respondents (38.10%) with high adherence, 10 respondents (47.62%) with moderate adherence and 3 respondents (14.29%) with low adherence. Comparison between pill count and MMAS-8 was carried out using the SPSS statistical program, and 50% result had expected count value less than 5, so did not qualify for chi-square (Ï‡2). Therefore, the Fisher exact test was done as the alternative way by viewing the exact-sig value in the column Fisher exact-test and obtained the value of 0.247 with a significance value of 0.05. So it shows there is no correlation between the measurements result of adherence with the method MMAS-8 and pill count.